A avaliação institucional na Universidade Federal do Tocantins (2004 - 2010) - GONÇALVES FILHO, Francisco (Universidade Federal do Pará, 2017)
This doctoral dissertation presents the research results regarding the relationship between university autonomy and the participation of university’s faculty, student body, and technical-administrative staff in the processes of institutional assessment at the Tocantins Federal University (UFT – Brazil), in the period 2004 through 2010, under the guidance of the National System of Higher Education Assessment – SINAES. The research objective was to analyze the implementation of SINAES at the UFT, in order to reveal the causes of the low turnout of the academic community in the assessment process, and its implications in the autonomy of the institution. The hypothesis was that institutional assessment at the UFT has been characterized by emptying the participation in the assessment process, for which reason it has served more the interests of the federal government and rectories in regulating and controlling the institution than the concerns of the university community. As for research methodology, case study was adopted; analyses of technical and normative documents, as well as conducting semi-structured interviews were used as data collection instruments. Results evidenced that SINAES, the assessment model adopted in the UFT, although self-declared formative, participatory, and integrative, proved to be oblivious to a broad participation of the university community, thus ineffective for the take of institutional awareness. In this way, such model has been marked by low participation, thereby jeopardizing the purposes of institutional assessment processes concerning issues like university autonomy, and community participation in such processes. The study found that institutional assessment has been conducted in a vertical form, which injures the autonomy of the institution, since it has followed, uncritically, whatever have been determined by the National System of Higher Education Assessment, and since it has been used rather as a mechanism of control and regulation than as a promoter of democratic participation within the institution, and improvement of the latter. Research findings allowed for the conclusion that a reformulation of institutional assessment policy should consider the strengthening of university autonomy, the broad participation of faculty, student body, and technical-administrative staff, as well as the improvement of infrastructure and budget necessary to the maintenance and expansion of public institutions of higher education.